Water Security in the Context of Sustainable Management of Transboundary Water Resources in the Caspian Region - R. A. Aliev (Vestnik MGIMO-Universiteta)
The paper examines water security in the Caspian region and the management of transboundary rivers for sustainable development. It analyzes the potential impacts of building dams on upper river courses on the region's water resources, particularly addressing concerns about environmental implications due to pollution from sources like sewage and agricultural fertilizers.It further investigates planned dam projects and their potential climate and ecological effects on the Caspian Sea and surrounding regions. The paper discusses the idea of desalination as a means to tackle water shortages but underscores its limitations in the closed hydrological system of the Caspian Sea.The primary focus lies in establishing effective management strategies for shared water resources. It introduces a novel perspective by considering these rivers and the Caspian Sea as an integrated water system, emphasizing the far-reaching consequences that excessive dam construction could pose to the overall hydrological balance. Collaboration and international agreements are crucial to navigate this challenge.The paper's significance lies in its innovative approach to water management, addressing the complex interplay between water, energy, food, and the environment in the region.